Enhanced magnetization in Y substituted Bi0.94Sm0.06FeO3 multiferroic ceramics - Al-Haj, Mansour (Kuwait Journal of Science, 2020)
The compounds Bi0.94Sm0.06FeO3, Bi0.92Sm0.06Y0.02FeO3, Bi0.90Sm0.06Y0.04FeO3, and Bi0.88Sm0.06Y0.06FeO3 were found to have the rhombohedral perovskite-like structure. The structural parameters were extracted from the X-ray diffraction data. The Fourier transform infrared spectroscopy revealed three absorption bands in the wavenumber range 400 – 2000 cm-1. The Bi0.94Sm0.06FeO3 and Bi0.92Sm0.06Y0.02FeO3 compounds were found to have similar weak ferromagnetic behaviors, whereas the ferromagnetism of the Bi0.88Sm0.06Y0.06FeO3 compound was found to be soft and substantially enhanced. The magnetic transition temperatures were in the range 340 – 350 °C.Physics